Spotlight on Data : Refactoring a Million-Line Codebase with Maude Lemaire - Lemaire, Maude (O'Reilly Media, Inc., 2020)
In late 2017, Slack's largest customers were plagued with relentless performance-related outages, due in part to the fact that public channels, private channels, and DMs were stored in completely distinct ways. Instead of shipping scrappy, short-term fixes, the company opted to address the root problem and completely refactor problematic functionality by consolidating any redundant database schemas. In this Spotlight on Data , Maude Lemaire explains how Slack succeeded by mapping out a precise plan that was careful to scope the effort to only its necessary components. Join in to learn real-world, successful techniques for modernizing your infrastructure from the ground up-live and in production. Recorded on November 18, 2019. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Data , you'll learn about, discuss, and debate the tools, techniques, questions, and quandaries in the world of data. You'll discover how successful companies leverage data effectively and how you can follow their lead to transform your organization and prepare for the Next Economy.